Empirical Analysis of Health Infrastructure, Health Expenditure and Economic Growth: A Case Study of Pakistan - Muhammad Niamat Ullah; Muhammad Waqar; Muhammad Ehsan Elahi; Saima Munir; Shehla Mazhar; Bushra Zaman; Saifullah Khan; Muhammad Rizwan; Kamran Ali; Mohsin Raza (Indus Journal of Social Sciences, 2025)
The present study was aimed at investigating empirical analysis of health infrastructure in terms of Hospital (Ht), Dispensary Unit (DUt), Rural Health Centre (RHCt), Health Expenditure and economic growth (GDPt) over a period of time 2003-04 to 2023-24. Augmented Dickey Fullert (ADF) Test found that tested dependent variable (i.e GDPt) was termed as stationary at level I(0) only, whereas the rest of independent variables (Ht, DUt, RHCt and HEt) were termed as stationary after applying 1st differencing. Findings of Ordinary Least Square (OLS) impacted positive influence and Auto-regressive distributed model revealed the positive and significant impact of Health Expenditure, negative impact of Hospital at lag(-2) and positive impact of Rural Health Centre at lag(-1) upon economic growth of Pakistan. Bound test indicated long run association among variables in the model. The value of the Error Correction Value is worked out as -0.59 termed statistically significant revealing convergence status from short run dynamics towards long run adjustments in the model. Variance Inflation Factor (VIF) indicated absence of severe multicollinearity, Heteroscedasticity Test, Lagrange Multiplier (LM) Test, Normality Test and Granger Causality Test termed significance of model. The study concluded that provision of health infrastructure and incurring expenditure significantly boosted economic growth by improving human capital and creation of job opportunities. Investments in health sector leads to maintain skilled and professionally capable workforce, resulting in reducing disruptions and increasing labor force participation.